2013
DOI: 10.1371/journal.pgen.1003246
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Dwarf8 on the Strengths and Weaknesses of Structured Association Mapping

Abstract: The strengths of association mapping lie in its resolution and allelic richness, but spurious associations arising from historical relationships and selection patterns need to be accounted for in statistical analyses. Here we reanalyze one of the first generation structured association mapping studies of the Dwarf8 (d8) locus with flowering time in maize using the full range of new mapping populations, statistical approaches, and haplotype maps. Because this trait was highly correlated with population structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 51 publications
5
90
0
Order By: Relevance
“…These LD and F st features led to the observed V-shape analytical power curve along the chromosome, particularly in the CF-Dent panel in which LD was more extended (Figure 1 and Figure 3). This is in good agreement with published manhattan plots of GWAS results, which showed a reduced number of low P-values in the centromeric regions (Bouchet et al 2013;Larsson et al 2013). In our three panels, we observed that this problem also arose with other classical estimators of relatedness (results not shown) such as the IBS estimator or the first estimator provided in Vanraden (2008, p. 4416) As MAF, F st , LD extent, and consequently CorK_Freq were different in the three panels (Table 1), average power was highly variable among the three panels (adjusted for the same population size).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These LD and F st features led to the observed V-shape analytical power curve along the chromosome, particularly in the CF-Dent panel in which LD was more extended (Figure 1 and Figure 3). This is in good agreement with published manhattan plots of GWAS results, which showed a reduced number of low P-values in the centromeric regions (Bouchet et al 2013;Larsson et al 2013). In our three panels, we observed that this problem also arose with other classical estimators of relatedness (results not shown) such as the IBS estimator or the first estimator provided in Vanraden (2008, p. 4416) As MAF, F st , LD extent, and consequently CorK_Freq were different in the three panels (Table 1), average power was highly variable among the three panels (adjusted for the same population size).…”
Section: Resultssupporting
confidence: 92%
“…For example F st and CorK_Freq had a stronger effect on power for markers with higher MAF, and MAF had a stronger effect on power for less differentiated markers. These results show that controlling false positives using the K_Freq model also implies reducing power at differentiated markers (Larsson et al 2013). It is interesting to note that no marker had a CorK_Freq ,0.03 (Figure 2).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, GWAS can be compromised when a great many gene products contribute to a complex trait and when kinship relationships are not taken into account. In maize, GWAS was used to find a strong correlation between the Dwarf8 locus and flowering time using a general linear model (Thornsberry et al, 2001), but the association was found to be spurious by association with population structure (Larsson et al, 2013). Nevertheless, models that correct for kinship have allowed the discovery of genes controlling many agronomic traits in rice (Oryza sativa; Huang et al, 2010) and sorghum (Morris et al, 2013).…”
Section: Limitations Of Gwas In the Selection Of Candidate Genes Frommentioning
confidence: 99%
“…This is also one of the rationales why we have constructed an automated workflow for simultaneously testing different models. It has also been suggested that the combination of traditional linkage analysis [32] and further haplotype analysis [33] can increase the power of GWA mapping to distinguish true from false associations.…”
Section: B Nested Association Mapping (Nam)mentioning
confidence: 99%